The happy orpheline - Carlson, Natalie Savage; Williams, Garth (New York Harper, 1957)
When the girls of the French orphanage visit the dog cemetery, Brigitte gets left behind and has an adventure with a woman whose husband is a pretender to the French throne.
Keywords: Orphans -- Fiction; France -- Fiction